2017
DOI: 10.1021/acs.joc.7b00148
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Palladium-Catalyzed Tandem Addition/Cyclization for the Construction of Indole Skeletons

Abstract: A palladium-catalyzed tandem addition/cyclization of 2-(2-aminoaryl)acetonitriles with arylboronic acids has been developed for the first time, achieving a new strategy for direct construction of indole skeletons. This system shows good functional group tolerance and remarkable chemoselectivity. In particular, the halogen (e.g., bromo and iodo) substituents are amenable to further synthetic elaborations thereby broadening the diversity of the products. Preliminary mechanistic experiments indicate that this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The Liao group described Pd-catalyzed addition of arylboronic acids to carbonic ester substituted nitriles to synthesize spirooxindolyl oxazol-2­(5 H )-ones . Our group developed a one-step syntheses of 2-arylbenzo­[ b ]­furans and 2-aryl-1 H -indoles via sequential addition and intramolecular annulation reactions with hydroxy- or amino-substituted 2-phenylacetonitriles. , …”
mentioning
confidence: 99%
“…The Liao group described Pd-catalyzed addition of arylboronic acids to carbonic ester substituted nitriles to synthesize spirooxindolyl oxazol-2­(5 H )-ones . Our group developed a one-step syntheses of 2-arylbenzo­[ b ]­furans and 2-aryl-1 H -indoles via sequential addition and intramolecular annulation reactions with hydroxy- or amino-substituted 2-phenylacetonitriles. , …”
mentioning
confidence: 99%
“…Chen et al have also reported a Pd-catalyzed addition/cyclization reaction cascade to construct the indole scaffold (Scheme 26), 38 albeit being different from the above work. In this reaction, they have introduced a nucleophile, the aniline moiety, to accomplish the cyclization.…”
Section: Short Review Syn Thesismentioning
confidence: 85%
“…2‐(Phenyl)‐5‐phenyl‐1H‐indole (28c): Colorless solid; 43.4 mg; yield 87 %. 1 H NMR (300 MHz, CDCl 3 ) δ 8.29 (br, 1H, N‐H), 7.77 (s, 1H), 7.60 (ddt, J = 8.3, 4.8, 1.8 Hz, 3H), 7.45–7.34 (m, 6H), 7.31–7.13 (m, 3H), 6.81 (s, 1H).…”
Section: Methodsmentioning
confidence: 99%